Women's experiences of border crossing: gender, mobility and border control. (3rd March 2020) - Matos, Raquel; Esposito, Francesca
In recent years, new migration patterns emerged in Europe and border control operations became more complex and broader, resulting in an increasing number of non-nationals detained for migration-related reasons. This paper aims to explore how gender, migration and border control intersect in the lives of women detained for not having authorisation to remain in Portugal. Several visits were made to a detention facility, where ten women detainees were interviewed. Our findings reveal how gender plays a crucial role in women's mobility pathways, and how the lack of a secure migrant status can be used as a control mechanism within the context of gendered relationships. Overall, due attention is paid to the way crossing borders impacts the lives of these women, reinforcing their vulnerabilities, and to the ways in which women deal with and resist the precariousness and violence they are exposed to, seeking a meaning and continuity for their lives.